ANALISIS STURKTUR KOGNITIF MAHASISWA PENDIDIKAN FISIKA PADA KONSEP STRUKTUR KRISTAL - Pasaribu, Marungkil (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
This research was a qualitative descriptive study aimed to describe the cognitive structure of physics education students were registered in Introduction to Solid State Physics course. Subjects numbered 38 people. Instrument used to determine the cognitive structure of students is a Word association test such as lattice, bases, crystal structure, unit cell, the symmetry of crystals, simple cubic (SC), body centered cubic (BCC), face centered cubic (FCC) and the Index Miller. The result showed that the cognitive structure of students on keywords simple cubic (SC), body centered cubic (BCC), and a face centered cubic (FCC) is more complete than other keywords. Factors affecting less complete cognitive structures among other students’ prior knowledge inadequate and difficult to describe the words contained in keywords. Keywords: cognivtive structure, analysis, crystal structure.